Rheophytism in Bornean Schismatoglottideae (Araceae) - Wong, Sin Yeng (2013)
The Schismatoglottid Alliance (tribes Schismatoglottideae, Cryptocoryneae and Philonotieae: Araceae) has been shown to be monophyletic in a previous study based on two cpDNA regions (matK and trnL-F). Here, ten additional taxa of Schismatoglottideae were sequenced, including two extra-Bornean Piptospatha species, and the type species of Hottarum, unavailable at the time of the previous analyses. Phylogenetic analyses were performed by using parsimony, likelihood (RAxML and likelihood ratchet PAUP*), and Bayesian inference to determine the placement of these additional taxa within Schismatoglottideae. The resulting tree topology supports, 1) a monophyletic West Sarawak clade comprising three genera: Aridarum, Bakoa, and Piptospatha; and 2) a supra-Lupar Line (the boundary between two of the known Bornean biochores) clade comprising the ‘Schismatoglottis’ josefii complex. Nineteen morphological, ecological, and geographical characters were coded and mapped using parsimony (unordered model) onto the Bayesian tree to investigate incidents of homoplasy or apomorphic status of morphologies presumed significant in the evolution of rheophytism. The morphologies proposed here as the primary mechanisms adaptive for rheophytism in Bornean Schismatoglottideae are: root/shoot disarticulation; a free ligular sheath; and marcescent senescence of the ligule. Two morphologies formerly used as generic definers, and previously treated as homologous: presence of a micropylar appendage, and thecae horns, are shown to be homoplastic